Maximum efficiency of induction motors considering iron loss resistance. Issue 9 (18th June 2019) - Ishikawa, Takeo; Qu, Haoyang; Kasahara, Kouki
Abstract : Although there was an extensive amount of research in the area of high efficiency control of induction motors, the equation of maximized efficiency has not been given. The relationship between the source frequency and the motor speed and the equation of efficiency have been derived when the efficiency is maximized for a given torque and speed, and then, they are verified using a single‐phase equivalent circuit considering iron loss resistance. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.